Pornography, ideology, and the internet : a Japanese adult video actress in mainland China - Zhang, Mei, 1981- (Lexington Books, 2019)
"This book investigates how a Japanese pornographic star can be treated as a cultural product and can be a window into the effects of the cross-cultural migration of cultural products. This in turn reveals that the transformative intermediaries play a significant role in the transformation of cultural products in China"--